Variability in retinoid-like activity of extracellular compound mixtures produced by wide spectra of phytoplankton species and contributing metabolites - Smutna, Marie; Vecerkova, Jaroslava; Priebojova, Jana; Pipal, Marek; Krauss, Martin; Hilscherova, Klara (Journal of hazardous materials, 2021)
Some phytoplankton species were shown to produce teratogenic retinoids. This study assessed the variability in the extracellular production of compounds with retinoid-like activity for 50 independent cultivations of wide spectra of species including 12 cyanobacteria (15 strains) and 4 algae of different orders. Extracellular retinoid-like activity was detected for repeated cultivations of six cyanobacteria. The results were consistent for some species including Microcystis aeruginosa and Aphanizomenon gracile. The detected retinoid-like activities ranged from below the limit of quantification of 16 ng/L to over 6 µg all-trans retinoic acid (ATRA) equivalent/L. Nontargeted virtual fractionation together with suspect screening approach enabled to identify some retinoid-like compounds in exudates, including ATRA, 9/13-cis retinoic acid, all-trans 5,6-epoxy retinoic acid, 4keto-ATRA, 4keto-retinal, 4hydroxy-ATRA, and retinal. Most of them were for the first time repeatedly detected in exudates of all studied algae (at ng/L levels) and cyanobacteria. Their relative potencies ranged from 0.018 (retinal) to 1 compared to ATRA. They accounted for less than 0.1-50% of total detected retinoid-like activity. The high detected activities and concentrations of retinoids in some samples and their direct accessibility from exudates document potential risk of developmental toxicity for organisms in proximity of massive water blooms.
Keywords: Phytoplankton; fytoplankton; Cyanobacteria; Retinoic acid receptor; Retinoid-like activity; retinoidy; Aphanizomenon; Retinoids; Microcystis; Exudates